Being Mortal: Medicine and What Matters in the End by Atul Gawande - Wei, Randy L. (Annals of Palliative Medicine; Vol 4, No 2 (April 30, 2015): Annals of Palliative Medicine, 2015)
In “Being Mortal”, physician and noted author, Dr. Atul Gawande, tackles the difficult subject of palliative care and end of life. How do “we” as a physician or “we” as a patient and society discuss this topic, so as to improve quality and not just quantity of life? With poignant memories from his experiences as a surgical oncologist at Brigham and Women’s Hospital, and from those he interviewed in the hospice and palliative care field, Dr. Gawande artfully explores the evolution of elder care, and provides insight and advice on how to skillfully initiate and navigate end of life and palliative care discussion. Society has changed wherein once